2013
DOI: 10.1371/journal.pone.0075898
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomic Analysis of Gingival Crevicular Fluid in Different Periodontal Conditions

Abstract: AimTo quantify the proteome composition of the GCF in periodontal health (HH) and in sites with different clinical conditions in chronic periodontitis (CP) subjects.Material and Methods5 subjects with HH and 5 with CP were submitted to full-mouth periodontal examination, and GCF sampling. Sites in the CP group were classified and sampled as periodontitis (P, probing depth, PD>4 mm), gingivitis (G, PD≤3mm with bleeding on probing, BOP), and healthy sites (H, PD≤3mm without BOP). GCF proteins were subjected to l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
101
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(118 citation statements)
references
References 29 publications
8
101
0
4
Order By: Relevance
“…Histones, which are DNA binding proteins, were discovered in this study similar to other investigations . Histones H2A, H2B and H4 all exhibited high chronic periodontitis/healthy and gingivitis/healthy ratios in this study as histones were not identified in the healthy group, supporting previous reports that levels of H2B in gingival crevicular fluid increase with experimental gingivitis and periodontitis .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Histones, which are DNA binding proteins, were discovered in this study similar to other investigations . Histones H2A, H2B and H4 all exhibited high chronic periodontitis/healthy and gingivitis/healthy ratios in this study as histones were not identified in the healthy group, supporting previous reports that levels of H2B in gingival crevicular fluid increase with experimental gingivitis and periodontitis .…”
Section: Discussionsupporting
confidence: 90%
“…It also enhances neutrophil production and adherence to tissues and polymorphonuclear leukocyte cell functioning . In accordance with this study, the higher levels of lactoferrin in the chronic periodontitis group as opposed to the healthy group confirm other gingival crevicular fluid analyses . Through its growth regulatory function, it inhibits lymphocyte proliferation, antibody production and decreases complement reaction in an effort to control inflammation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It is well known that there are some di erences in the proteins found in GCF collected from clinically healthy sites and sites with chronic periodontitis. [3][4][5] Protein contents in GCF are commonly analyzed by enzyme-linked immunosorbent assay (ELISA), but there is a limitation in the number of proteins that can be analyzed at one time. Also, conventional methods for analyzing non-protein or novel molecules are time-consuming and may require multiple techniques (and also instrumentation for each technique) to gain a complete analyte pro le useful for prediction and diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the promising prospects of using whole saliva for screening for periodontal diseases, most proteomic studies have been confined to 2-D-gel electrophoresis approaches that only used MALDI and electrospraymass spectrometry for identification of protein spots [28][29][30][31]. Only few studies have used the highly sensitive gel free LC-MS/MS approaches for studying periodontitis-related changes in the composition of whole saliva GCF, and periodontal tissues [32][33][34][35]. The most frequently detected proteins in these studies were actins, keratins, histones, annexins, protein S100-A9, HSPB1, LEG7 and 14-3-3, apolipo protein A-I, ALB protein, albumin and serum albumin.…”
Section: Proteomic Biomarkers In Periodontal Diseasementioning
confidence: 99%